2021
DOI: 10.3390/dj9070078
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Water Storage on Hardness and Interfacial Strength of Resin Composite Luting Agents Bonded to Surface-Treated Monolithic Zirconia

Abstract: Background: Durable bonding between resin composite luting agents (CLA) and zirconia is still a matter of controversy. The purpose of this study was to evaluate the effect of water storage on hardness and interfacial strength of three CLA, a non-adhesive (Multilink Automix/ML), an adhesive (Panavia F 2.0/PF) and a self-adhesive (PermaCem 2.0/PC), bonded to polished (CL) and grit-blasted (AL: 50 μm alumina, SJ: Sil-Jet + Monobond Plus silane) monolithic zirconia surfaces. Methods: CLA specimens (n = 5/cement, c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 37 publications
0
3
0
Order By: Relevance
“…Furthermore, Lümkermann et al [48] concluded that plasma treatment cannot substitute for sandblasting to the zirconia bonding. Moreover, a previous study reported similar SBS values to those obtained in the present study for the Zr-CP group, with the same primer and cement for specimens subjected to tribo-chemical silica coating with Silk-Jet powder [51].…”
Section: Discussionsupporting
confidence: 89%
“…Furthermore, Lümkermann et al [48] concluded that plasma treatment cannot substitute for sandblasting to the zirconia bonding. Moreover, a previous study reported similar SBS values to those obtained in the present study for the Zr-CP group, with the same primer and cement for specimens subjected to tribo-chemical silica coating with Silk-Jet powder [51].…”
Section: Discussionsupporting
confidence: 89%
“…Moreover, glazing and sandblasting processes have minimal influence on the crystallographic structure phases [45]. However, an increase in roughness (Sa, Sz) was observed after sandblasting [46]. Kim et al reported that translucent zirconia requires 50 µm alumina sandblasting to prevent surface damage [47].…”
Section: Discussionmentioning
confidence: 99%
“…Numerous studies have been conducted to determine the effect of femtosecond laser irradiation on dental zirconia ceramics [ 11 , 12 , 15 , 16 , 17 , 18 , 19 , 20 , 21 ]. Tzanakakis et al, investigated the shear bond strength of femtosecond laser-irradiated highly translucency zirconia (5Y-PSZ) to composite cement [ 19 ]. They concluded that the FL treatment of 5Y-PSZ ceramics is a viable alternative for mechanical cement retention.…”
Section: Discussionmentioning
confidence: 99%